Survey of antimicrobial resistance in clinical Burkholderia pseudomallei isolates over two decades in Northeast Thailand. - Wuthiekanun, V; Amornchai, P; Saiprom, N; Chantratita, N; Chierakul, W; Koh, G; Chaowagul, W; Day, N; Limmathurotsakul, D; Peacock, S (2011)
A 21-year survey conducted in northeast Thailand of antimicrobial resistance to parenteral antimicrobial drugs used to treat melioidosis identified 24/4,021 (0.6%) patients with one or more isolates resistant to ceftazidime (n = 8), amoxicillin-clavulanic acid (n = 4), or both drugs (n = 12). Two cases were identified at admission, and the remainder were detected a median of 15 days after starting antimicrobial therapy. Resistance to carbapenem drugs was not detected. These findings support the current prescribing recommendations for melioidosis.